Production of High‐Melting Symmetrical Monounsaturated Triacylglycerol‐Rich Fats from Mango Kernel Fat by Acetone Fractionation. (18th December 2016) - Jin, Jun; Mu, Hongyan; Wang, Yue; Pembe, Warda; Liu, Yijun; Huang, Jianhua; Jin, Qingzhe; Wang, Xingguo
Abstract: 1, 3‐Distearoyl‐2‐oleoyl‐glycerol, 1‐palmitoyl‐2‐oleoyl‐3‐stearoyl‐glycerol and 1‐stearoyl‐2‐oleoyl‐3‐arachidoyl‐glycerol are typical high‐melting symmetrical monounsaturated triacylglycerols (Hm‐SMT) found in cocoa butter improver (CBI). These triacylglycerols help to increase the hardness of chocolate products in tropical climates. In the present study, natural CBI products were produced from mango ( Mangifera indica, Linn) kernel fat (MKF) by selective three‐stage fractionation using acetone. The second stearin (fraction I) from the first precipitate of MKF by fractionation for 180 min at 15 °C contained 86.9% of Hm‐SMT, and the third stearin (fraction II) obtained from fraction I by further fractionation for 180 min at 18 °C was enriched with 94.4% Hm‐SMT. High percentages of such triacylglycerols in these products contributed to higher slip melting points (36.5–37.7 °C) than commercial cocoa butter and cocoa butter equivalent (26.7 and 27.9 °C). Also, their differential scanning calorimetry properties and solid fat content values were superior to those in traditional confectionery fats, indicating that the tailored stearins could be used as ideal CBI. In particular, the hard fat blends consisting of 55–70% cocoa butter (CB) and 30–45% fraction II were considered as the preferred heat‐resistant chocolate ingredients. In addition, the mixture of the oleins (fraction III) was rich in diunsaturated and triunsaturated triacylglycerols and showed similar thermal properties to super palm oil, thus making it more suitable as special fat ingredients and modified fat sources.